Pleural involvements in pulmonary sarcoidosis: A case report and review of the literature - Ji, Xiaoqing; Lu, Jiameng; Zuo, Anli; Sun, Fei; Peng, Haiying; Lu, Degan (Frontiers in Medicine, 2022)
As a chronic and multisystemic granulomatosis of unknown origin, sarcoidosis can affect multiple organs throughout the body with variable progression and prognosis. Sarcoidosis may present with a battery of symptoms and signs, such as dyspnea, non-productive cough, uveitis, and erythema nodosum. Although the lungs and mediastinal lymph nodes are almost affected in sarcoidosis, involvements of the pleurae remain uncommon. Herein, we report a case of sarcoidosis with both pleural effusions and pleural nodules as confirmed by thoracoscopic pleural biopsy.